Association between brain structures and migraine: A bidirectional Mendelian randomization study - Guo, Xiaoming; Wang, Dingkun; Ying, Caidi; Hong, Yuan (Frontiers in Neuroscience, 2023)
Background Accumulating evidence of clinical and neuroimaging studies indicated that migraine is related to brain structural alterations. However, it is still not clear whether the associations of brain structural alterations with migraine are likely to be causal, or could be explained by reverse causality confounding. Methods We carried on a bidirectional Mendelian randomization analysis in order to identify the causal relationship between brain structures and migraine risk. Summary-level data and independent variants used as instruments came from large genome-wide association studies of total surface area and average thickness of cortex (33,992 participants), grey matter volume (8,428 participants), white matter hyperintensities (50,970 participants), hippocampal volume (33,536 participants), and migraine (102,084 cases and 771,257 controls). Results We identified suggestive associations of the decreased surface area (OR = 0.85; 95% CI, 0.75-0.96; P = 0.007), and decreased hippocampal volume (OR = 0.74; 95% CI, 0.55 - 1.00; P = 0.047) with higher migraine risk. We did not find any significant association of grey matter volume, cortical thickness or white matter hyperintensities with migraine. No evidence supporting the significant association was found in the reverse MR analysis. Conclusions We provided suggestive evidence that surface area and hippocampal volume are causally associated with migraine risk.